Islamic and Spirituality: Reevaluating Maslow’s Hierarchy for Self-Actualization - Ulfatun Wahidatun Nisa; Amal Fathullah Zarkasyi (Universitas Muhammadiyah Malang, 2024)
This article explores the Maslow’s Hierarchy of Needs – Self Actualization also study aims to examine the thoughts brought by Western figures related to Hierarchy of Needs Abraham Maslow in Islamic Perspective which the most idea comes from Al Ghazali’s tought. The hierarchy of needs consisting with five elements, there are: First, physiological needs are the most basic needs in Abraham Maslow's hierarchy. Second, the need for security, Third, social needs occupy Fourth, the need for gratitude Fifth, self-actualization needs are the highest ranked needs in Abraham Maslow's hierarchy. Maslow describes self-actualization by providing emphasis on full-humanness, arising from the development of human biological nature, and in accordance with their birth destiny. The conclusion that we can write here is The Islamic ontological perspective is not incorporated in Maslow’s hierarchy of needs. In addition to the alleged ethnocentrism, non-universality and invalidity, the following mindsets distinguish Maslow’s theory from an Islamic point of view: (a) materialistic-based, (b) the absence of spiritual aspect and different interconnectedness between material and spiritual needs, and world-orientation, disregarding the hereafter.But, Islam can elaborate Maqasid al-Syari’ah (the objectives of Islamic law), human needs are grouped into three descending categories of significance: dharuriyyat (essential), hajiyyat (complementary), tahsiniyyat (embellishment). Dharuriyyat is the must-exist necessities that if not fulfilled will result in an imperfect human life as well as threaten the safety of humanity both in this world and the hereafter. This is inherent in the preservation of religion, life, intellect, progeny, and wealth. Hajiyyat is the complementary needs to remove hardships that are contained in the process of satisfying the necessities. Tahsiniyyat refers to things that embellish people’s lives by adding quality to the necessities.